2019
DOI: 10.5688/ajpe6519
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Renal Replacement Therapy Simulation to Strengthen Essential Pharmacist Skills

Abstract: Objective. To assess third-year pharmacy students' knowledge and application of renal pharmacotherapy using a renal replacement therapy (RRT) simulation. Methods. A simulation was developed that involved three stations related to RRT: peritoneal dialysis, continuous renal replacement therapy (CRRT), and hemodialysis. Stations involved demonstration of each modality, literature searches for drug information questions related to renal dosing with written recommendations, and utilization of an electronic medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…However, in one study evaluating a pediatric acute care simulation conducted for medical students through remote instruction, there was a significant improvement in student teamwork performance that was found to be similar to traditional, locally facilitated SBL activities 5 . Although not addressed in our SBL activity, a remote SBL activity may have the potential to overcome geographical limitations, such as faculty manpower, which is a common barrier to implementing SBL across pharmacy education 6,7 . In another study conducted with medical students, Hayden et al compared the impact of simulation sessions facilitated by in‐person faculty vs those supervised remotely using web‐conferencing software (WebEx[Cisco, San Jose, California]) and found that telecommunication successfully enhanced access to simulation‐based instruction 8 .…”
Section: Discussionmentioning
confidence: 93%
“…However, in one study evaluating a pediatric acute care simulation conducted for medical students through remote instruction, there was a significant improvement in student teamwork performance that was found to be similar to traditional, locally facilitated SBL activities 5 . Although not addressed in our SBL activity, a remote SBL activity may have the potential to overcome geographical limitations, such as faculty manpower, which is a common barrier to implementing SBL across pharmacy education 6,7 . In another study conducted with medical students, Hayden et al compared the impact of simulation sessions facilitated by in‐person faculty vs those supervised remotely using web‐conferencing software (WebEx[Cisco, San Jose, California]) and found that telecommunication successfully enhanced access to simulation‐based instruction 8 .…”
Section: Discussionmentioning
confidence: 93%